2018
DOI: 10.1055/s-0038-1672121
|View full text |Cite
|
Sign up to set email alerts
|

Is Arthrodesis a Reliable Salvage Option following Two-Stage Revision for Suspected Infection in Proximal Tibial Replacements? A Multi-Institutional Study

Abstract: The aim of this multicentric retrospective study was to verify whether knee arthrodesis (KA) is a viable reconstructive option after two-stage revision for infection of proximal tibia (PT) endoprosthetic reconstruction (EPR). Sixty patients who underwent a two-stage revision were included. Definitive EPR or a KA with a modular system was performed following consideration of soft tissue and extensor mechanism conditions. Patients were evaluated with Musculoskeletal Tumor Society Score and Oxford Knee Score. Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Studies in the literature have reported on three different silver-coated MPs [ 97 ], with most of the data coming from oncologic patient series. Fiore et al [ 98 ] highlighted that silver-coated implants are particularly useful in two-stage revisions for infection and in patients with incidental positive cultures at the time of prosthesis implantation [ 64 , 98 , 99 , 100 , 101 , 102 ]. On the other hand, the results of silver-coated MPs in PJI prevention are extremely heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature have reported on three different silver-coated MPs [ 97 ], with most of the data coming from oncologic patient series. Fiore et al [ 98 ] highlighted that silver-coated implants are particularly useful in two-stage revisions for infection and in patients with incidental positive cultures at the time of prosthesis implantation [ 64 , 98 , 99 , 100 , 101 , 102 ]. On the other hand, the results of silver-coated MPs in PJI prevention are extremely heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical intravenous broad-spectrum antibiotic therapy is generally begun immediately after surgery. After culture results, antibiotic therapy is modified, using an oral regimen whenever possible [ 10 ].…”
Section: Introductionmentioning
confidence: 99%